(untitled) (Research, Society and Development, 2020)
The present work deals with a pedagogical experience entitled “Crateús in the fight against racism”, held in a non-formal educational space, in December 2018, in the municipality of Crateús / CE. It aims to address the concepts of prejudice, racism and intolerance and to present the Brazilian legal apparatus that deal with equality and the dignity of the human person, such as the Federal Constitution of 1988, the “Caó” Law and the Racial Equality Statute. In the educational field, it highlights the importance of Law 11,645 / 2008, which includes in the official curriculum of the education network the mandatory theme of Afro-Brazilian and Indigenous History and Culture. Through descriptive research, with a qualitative approach, this article brings up reflections on the event, which took place in a public square and was designed, built and carried out by representatives of several institutions and aimed at the entire population. The activity aimed to generate a reflection on the theme of racism and the necessary movement of resistance and struggle to affirm, consolidate and expand the rights of the black population. Using spaces that are not the classroom and privileging other actors in the teaching and learning process that are not teachers and students, proved to be potentializers in carrying out reflective and educational actions.